The cognitive processing of candidates during reading tests: Evidence from eye-tracking. (October 2013) - Bax, Stephen
The research described in this article investigates test takers' cognitive processing while completing onscreen IELTS (International English Language Testing System) reading test items. The research aims, among other things, to contribute to our ability to evaluate the cognitive validity of reading test items (Glaser, 1991; Field, in press). The project focused on differences in reading behaviours of successful and unsuccessful candidates while completing IELTS test items. A group of Malaysian undergraduates ( n = 71) took an onscreen test consisting of two IELTS reading passages with 11 test items. Eye movements of a random sample of these participants ( n = 38) were tracked. Stimulated recall interview data was collected to assist in interpretation of the eye-tracking data. Findings demonstrated significant differences between successful and unsuccessful test takers on a number of dimensions, including their ability to read expeditiously (Khalifa & Weir, 2009), and their focus on particular aspects of the test items and texts, while no observable difference was noted in other items. This offers new insights into the cognitive processes of candidates during reading tests. Findings will be of value to examination boards preparing reading tests, to teachers and learners, and also to researchers interested in the cognitive processes of readers.